Environment, agro-system and quality of food production in Italy - Dal Ferro, Nicola; Borin, Maurizio (Italian Journal of Agronomy, 2017)
In the context of increasing attention towards sustainable and high quality food products, Italy plays a key role in Europe due to its embedded territorial vocation for locally produced food and alternative agriculture systems helping biodiversity and landscape preservation. Here, we report an overview of Italian agriculture by analysing organic farming (OF) and geographical indication (GI) systems and their contribution to the national agriculture. Land use data highlight that OF and GI contribute around 10% to the utilised agriculture area (UAA), with relevant distinctions in terms of regional distribution. While GIs are mostly in the north-central regions (8.5%), OF products are most frequent in the south and on the islands (5.0% of UAA). This trend was observed on the one hand in Trentino-South Tirol, Veneto and Friuli-Venezia Giulia (%UAA GI/%UAA OF>5.9), and on the other in Calabria, Basilicata and Sicily (%UAA GI/%UAA OF<0.1). Similarly, both systems are widespread in less-favoured areas in terms of agricultural intensification, providing support to preserve agro-systems and reduce land abandonment.